RESPON PERTUMBUHAN DAN PRODUKSI TANAMAN BIT MERAH (Beta Vulgaris L.) DI DATARAN RENDAH TERHADAP PEMBERIAN PUPUK ORGANIK CAIR DAN PUPUK KANDANG KAMBING - Muhammad Dwi Nuryanto (Agrisia: Jurnal Ilmu-Ilmu Pertanian, 2022)
This research was conducted on an area of ​​150 m² which is located in the AD Zeni Central Warehouse Dormitory, Jl. Raya Cileungsi-Jonggol KM.7, Kel. Gandoang, Kec. Cileungsi, Kab. Bogor. This research will be conducted in April 2022 – July 2022. This study used a factorial two-factor Randomized Block Design (RAK) with the first factor being liquid organic fertilizer and the second factor being goat manure. The data obtained will then be further tested using the Duncan Multiple Range Test (DMRT) at a level of 5%. The results showed that there was an interaction effect of giving concentration of liquid organic fertilizer and dose of goat manure on the growth of plant height and leaf length of beetroot. The concentration of liquid organic fertilizer affects the growth of plant height, leaf length, number of leaves, tuber diameter, and tuber weight. Administration of goat manure has an effect on plant height growth, leaf length, number of leaves and tuber weight. Keywords: beet, organic fertilizer, liquid organic fertilizer and goat manure.